Breaking Barrier of Perplexity: How AI Tackles Brainstorming in Academic Writing - Anggytha Mutiara; Diva Maulida; Lilia Indriani (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2024)
Artificial Intelligence has become a hot topic in recent years, with increasing interest in its potential as a writing aid. Brainstorming ideas has been a challenge for students in writing articles. Furthermore, with the development of Artificial Intelligence, such as Perplexity as a writing aid, it can elaborate new ideas in brainstorming accompanied by relevant sources and make writing articles more efficient. This study reports students’ perspective towards Perplexity as Artificial Intelligence to brainstorm ideas in academic writing. Qualitative methods with interviews as the instrument was used in doing the research. The sample is from the English Department Study Program in one of the Universities in Central Java, Indonesia. To gather the data for this research, close-ended and semi-structured interviews are combined to gain more information. The results explored the challenges of Artificial Intelligence in teaching and learning in 5.0 society. Moreover, AI can be a useful tool in facilitating the brainstorming process, there are still some barriers that need to be overcome.